Analisis Keuntungan Usaha Gula Aren Dan Usaha Cap Tikus Di Desa Raanan Lama Kecamatan Motoling - Givany M. Mahipe; Joachim N. K. Dumais; Olfie L. S. Benu (AGRI-SOSIOEKONOMI, 2022)
This research aims to compare the benefits of business made from sap raw, including palm sugar business and “cap tikus” business in Raanan Lama Village, Motoling District. This research was carried out from October 2021 to December 2021 in Raanan Lama Village, Motoling District. The data used in this study are primary data and secondary data. Primary data were obtained from direct interviews with farmers and secondary data from the local government in Raanan Lama Village. The number of samples in this study were 14 people, 7 people for the “cap tikus” business and 7 people for the palm sugar business. This study was analyzed descriptively using the profit method. The results showed that the profit of the rat stamp business was higher than the profit of the palm sugar business. Because the working time of the mouse stamp business is faster than the palm sugar business and the production cost of the mouse stamp business is smaller.